The phonological development of typically developing first language Zulu-speaking children aged 2;6 - 6;5 years : a descriptive cross-sectional study - Jeggo, Zenia M (Division of Communication Sciences and Disorders, 2016)
Background: Zulu, one of the eleven official languages in South Africa, is the most spoken language in the country. However, research on children's phonological development in Zulu is minimal. To date there are no published Zulu speech assessments and associated normative data that speech-language pathologists (SLPs) can use to identify children with speech sound disorders who speak this language. Method: This descriptive, cross-sectional study aimed to document the phonological development of thirty-two typically developing first language Zulu-speaking children between 2;6 and 6;5 years. Participants attended school or crèche in Manguzi, KwaZulu-Natal, and were grouped into six month age categories. A single-word Zulu phonology assessment was developed and used to assess the participants. Assessments were audio recorded, and field transcriptions made using the International Phonetic Alphabet (IPA). Speech development was described in terms of phoneme acquisition, word shape, phonological processes and percentage of vowels (PVC) / consonants correct (PCC). Consonant acquisition was assessed in the penultimate syllable only, according to the structure of Zulu.